World Military Expenditures and Arms Transfers, 1968-1977 ([Verlag nicht ermittelbar], 1984)
This data collection contains world military expenditures and arms trade data for 140 countries in the period 1968-1977. Data are provided for national military expenditures, including the value of weapons exports and imports in millions of United States dollars, as well as for population characteristics. Various socioeconomic data are presented to provide a comparative background for the series. Data are provided on the gross national product (GNP), military expenditures, central government expenditures, public health expenditures, and public education expenditures. Additional variables provide information on the number of soldiers, teachers, and doctors per 1,000 population, and total imports and exports of other goods and services.